PREVALENCE OF TUBERCULOSIS IN KOTLI, AZAD KASHMIR - Saleem, Mohammad; Ahmad, Waseem; Jamshed, Fareeda; Sarwar, Javed; Gul, Nasreen (Journal of Ayub Medical College Abbottabad, 2013)
Background: Tuberculosis is highly prevalent in Pakistan. It is a contagious disease and causes a lot of morbidity and mortality. Its treatment is costly especially for poor countries like Pakistan. But fortunately it is a preventable disease. Objective of this study was to analyse various epidemiological features of tuberculosis in District Kotli, a remote area of Northern Pakistan. Methods: This cross sectional study was conducted in District Kotli, Azad Kashmir from January to December 2009. Data was collected from eight national TB centres of District Kotli. It included all the diagnosed cases of tuberculosis, registered there during the study period. Various epidemiological aspects of these patients were analysed. Results: Total number patients registered during the study period were 752. Of these 579 (76.99%) were pulmonary and 173 (23%) were extra-pulmonary tuberculosis (EPT). Total prevalence of tuberculosis was found to be 100.27 per 100,000. Prevalence of pulmonary TB was 77.2 while that of EPT was 23.07 per 100,000. There were 405 males (53.85%) and 347 females (46.14%). Most patients were 61-75 years of age (220, 29.25%). Overall 417 (55.44%) were 46-75 years. Housewives were affected most frequently (324, 43.08%). Labourers were also commonly involved (40.82%). All cause mortality was 29 (3.85%). Mortality due to tuberculosis was 11 (1.04%). Among pulmonary tuberculosis, 259 (44.78%) were sputum smear positive and 320 (55.26%) were sputum smear negative. In EPT, most frequent was pleural effusion (74, 42%) and least frequent was skin involvement (3, 1.73%). Conclusion: Prevalence of tuberculosis in Kotli was lower than the overall prevalence in Pakistan. Male to female ratio was lower than that generally observed in Southeast Asia. It was more common in middle to old age population. Frequency was higher in housewives and labourers. Very significant proportion of pulmonary TB was sputum smear positive. Among EPT, pleural effusion was the most common mode of presentation. Keywords: Tuberculosis, Prevalence, Azad Kashmir, Extra-pulmonary tuberculosis, Mortality, Pakistan